Southern Ocean sea ice, icebergs, and meteorological data from maritime sources for the period 1929 to 1940 - Divine, Dmitry V.; Divina, Svetlana; Bjørge, Ole Edvard; Isaksson, Elisabeth; Jølle, Harald Dag; Stokkeland, Ivar; Vasquez Guzman, Mariela; Wilkinson, Sally; Wilkinson, Clive (Geoscience Data Journal, 2024)
Maritime historical documentary sources of weather and state of sea surface including sea ice can aid in filling a known climate knowledge gap for the Southern Ocean and Antarctica for the first half of the 20th century. This study presents a data set of marine climate, sea ice and icebergs recovered from a collection of logbooks from mainly Norwegian whaling factory ships that operated in the Southern Ocean during 1929-1940. The data set comprises some 8000 weather and 4000 sea ice/open sea records from austral summers of the study period. This paper further discusses the structure and content of most common Norwegian maritime documentary sources of the period along with the practices of logging information relevant for the study, such as time keeping, positioning and making weather observations. An emphasis was made on recovery of notes on sea ice and icebergs and their interpretation in terms of WMO categories of sea ice concentration. Data, including ship-related metadata from all individual documents are homogenized and structured to a common machine-readable format that simplifies its ingestion into relevant climate data depositories.
Keywords: Sørishavet; hvalfangst; isberg; klima; meteorologi; sjøis; skipsloggbøker

Perspectives on the economic and political history of the Ross Sea - Basberg, Bjørn L.; Lintott, Bryan (The Polar Journal, 2023)
The paper analyses the economic and political history of the Ross Sea, where exploration, science, commercial exploitation, politics and adventure became highly interlinked and interwoven. Expedition accounts and the extensive literature on Antarctic history and politics inform the contextual aspects. The archives of the Norwegian whaling company A/S Rosshavet, established in 1923, and the United States of America and New Zealand archival material from the 1950s are key sources. From the first whaling season onwards, the impact of Antarctic whaling, and later scientific bases, highlights and illustrates the tensions between Antarctic commerce, territorial claims and international politics.
Keywords: Sørishavet; historie; hvalfangst; politikk; økonomi

Utryddelsen : historien om den norske industrielle hvalfangsten - Ytreberg, Espen (Press, 2023)
Det var det første norske oljeeventyret. I dag snakker ingen om det. I drøye hundre år etter at Svend Foyn oppfant granatharpunen i 1863, var Norge pådriver, innovatør og profitør i den største nedslaktingen av ville dyr verden noensinne har sett: Den globale industrielle hvalfangsten. Norge utviklet teknologi, åpnet nye fangstfelt og arbeidet internasjonalt for å hindre regulering og begrensninger. Da hvalfangstens epoke var over, var nesten ingen igjen av hvalene som hadde fylt verdenshavene. I dypet rådet en ny stillhet. Langs strendene i Sørishavet lå bare de råtnende hvalskrottene igjen. Men de norske hvalfangstrederne hadde blitt rike. Vanlige norske arbeidere bemannet den norske hvalfangstindustriens hvalkokerier og hvalbåter. For disse mennene var arbeidet slit, eventyr og mareritt. Etter dem finnes et stort materiale - fotografier, dagbøker, brev - som forteller om arbeidernes erfaringer fra slaktesonene i Sørishavet. I Utryddelsen forteller Espen Ytreberg historien om den norske hvalfangsten fra arbeidernes perspektiv. Han tar oss med på fangsten, lar oss følge arbeidernes opplevelser, setter bildene og beretningene deres inn i en større historisk sammenheng. Utryddelsen er et enestående stykke historieskriving om et avgjørende kapittel i norsk historie - en bok som åpner den nære norske fortiden opp for oss på helt nye måter.
Keywords: Sørishavet; hvalfangst

Norway's path to the Antarctic Treaty - Jølle, Harald Dag (Fram forum, 2021)
Keywords: Antarktis; Antarktistraktaten 1959; Norge; ekspedisjoner; historie; hvalfangst; internasjonal; jus; politikk